Cells take a break when they are TIARed. (11th December 2018) - Altmeyer, Matthias
Abstract : Cell cycle progression relies on controlled transition from one phase of the cell cycle to the next, and sensing whether or not a certain cell cycle phase has been completed before the next phase is allowed to start is crucial for genome integrity and cell survival. In this issue of EMBO Reports, Lafarga et al 1 report an original mechanism for spatio‐temporal control of CDK1 activity, which depends on a nuclear function of the RNA‐binding protein TIAR. The role of TIAR to restrain mitotic onset is linked to a newly discovered membraneless compartment, termed G2/M transition granule (GMG), which transiently sequesters CyclinB‐CDK1 in response to replication stress to curb CDK1 kinase activity and thereby tune G2 duration and mitotic commitment. Abstract : The RNA‐binding protein TIAR accumulates in nuclear G2/M transition granules induced by replication stress. Upon G2/M checkpoint activation TIAR transiently sequesters CDK1 in GMGs to curb CDK1 activity and tune G2 duration and mitotic commitment.